Clinico-haematological features of dermatophilosis in indigenous breeds of cattle in Ibadan, Nigeria (2018)
This study evaluated the clinical-hematological profiles in bovine dermatophilosis. A total of 50 dermatophilosis infected cattle were studied clinically and 50 blood samples taken from two different locations of Akinyele cattle market and Bodija Abattoir Ibadan. Hematological parameters such as PCV, Hb, RBC,WBC,Platelets, MCV, MCH, MCHC, Lymphocyte and Neutrophils were evaluated using standard procedures .The level of severity was classified based on the extent of the surface lesions and the chronicity as observed on the animals vis a viz body condition scoring system, hematological parameters under different breeds, sexes, ages and severity of disease condition were subjected to a one way analysis of variance (ANOVA) with no level of significance established at p < 0.05. White Fulani was the breed with the highest cases of dematophilosis (66%), females (86%) were more infected than males. Cattle within age bracket of 2-2½ years (38%) showed clinical signs of dermatophilosis more than other age groups. Sokoto Gudali breed had the highest values for most hematological parameters, while Kuri breed had the least values for most of the hematological parameters. Females showed better values than males. Age range 3-3½ years had most of the highest values. Mild infestation showed the highest values. Therefore, this study has been able to revealed variation to dermatophilosis susceptibility, Kuri breed, adult cattle and bulls appeared to be more resistance. The hematology in generalized dermatophilosis have been elucidated by this present study and have been found to vary with age, sex, severity of infection and breed of cattle.